Calla palustris (Araceae): New palynological insights with special regard to its controversial systematic position and to closely related genera. Issue 4 (27th December 2018) - Ulrich, Silvia; Hesse, Michael; Bröderbauer, David; Bogner, Josef; Weber, Martina; Halbritter, Heidemarie
Abstract: Almost all systematic treatments agree that Calla is a puzzling case, being a highly autapomorphic taxon with obscure relationships. In molecular–based classifications the variable placements of Calla within Aroideae conflict strongly with those in morphologically and anatomically based systematic classifications, which treat the genus as a subfamily (Calloideae) of its own. We studied the pollen morphology and ultrastructure of Calla by light and electron microscopy, and mapped the relevant pollen characters as well as some flower characters to the proposed placements of Calla within the Araceae as indicated in the various molecular phylogenies. Calla pollen is extraordinary within the entire Araceae. Pollen grains are small, and basically disulcate or with a ring–like aperture. The ornamentation is psilate to perforate, and the pollen wall consists of a sporopolleninous tectate–columellate exine. These pollen characters are shared with those of several earlier–diverging aroid taxa, especially with those of subfamily Zamioculcadoideae, whereas pollen characters in members of subfamily Aroideae deviate significantly. These findings are in accordance with other floral characters. Therefore, we propose that Calla is best placed in a transition zone between either subfamily Zamioculcadoideae ( Stylochaeton clade) and subfamily Aroideae (Aroideae clade) or between subfamily Zamioculcadoideae ( Stylochaeton clade) and subfamily Lasioideae.